ARTIFICIAL INTELLIGENCE AND THE FUTURE OF ENGLISH LANGUAGE USE - Jaloldinov Islomiddin Shamsitdin o‘g‘li; Baxtiyora Dilyora Azizjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The rapid development of Artificial Intelligence (AI), especially Large Language Models (LLMs) such as ChatGPT, has significantly reshaped the use of English in education and global communication. This study examines both the advantages and potential risks of AI in language learning. On the one hand, AI supports personalized learning, improves writing skills, and provides immediate feedback. On the other hand, it contributes to linguistic standardization, reduces diversity, and introduces algorithmic bias, particularly affecting non-native speakers. The research also highlights the growing digital divide caused by the dominance of English in AI systems. Based on recent studies and global reports, this article proposes the concept of “AI fluency” as a necessary skill for both students and educators to use AI critically and responsibly.